Indigenous Music Mediation with Urban Khmer: Tampuan Adaptation and Survival - Saurman, Todd (Journal of Urban Culture Research, 2014)
This paper describes some lowland/highland Khmer points of interconnection for indigenous Tampuan communities from the highland Northeast, Cambodia. Tampuan community musicians respond constructively to a Siem Reap tourist cultural show that depicts their indigenous ethnolinguistic group. Tampuan musicians make trips to the urban center of Phnom Penh to represent themselves in a CD recording, a concert, and a TV program. I contend that some community members are expressing strong cultural values as they mediate with the national and urbanculture in spite of a history of Khmerization efforts by lowland Khmer. A strong value of mediation reinforces highland desires to communicate with outsiders perceived as having great effect on highland everyday life. Meanwhile some urban Khmer who may mourn the loss of Khmer traditional culture and support its revival have demonstrated interest in the traditional cultures of Khmer highland communities as they possibly empathize with others perceived to be experiencing levels of alienation and marginalization similar to their own.